Levels of Adipokines in Blood of Woman with Threatened Abortion - A. V. Shestopalov; A. S. Shul’ga; A. N. Rymashevskij; I. M. Staviskij; A. A. Aleksandrova; T. P. Shkurat (Медицинский вестник Юга России, 2012)
Purpose: To investigate levels of adipokines and indicators of carbohydrate metabolism in the blood of women with a true threat of pregnancy termination (isthmico-cervical insufficiency). Materials and Methods: The study involved women in the period of 16 – 26 weeks of gestation – 18 women with a true threat of termination of pregnancy and 52 women with physiological pregnancy. Both groups were compared with levels of leptin, resistin, adiponectin, fasting glucose, fasting insulin and homeostasis model assessment of insulin resistance (HOMA-IR). Results: In the blood of women with a real threat of pregnancy termination are revealed significant changes in carbohydrate metabolism – the increase in levels of fasting insulin and glucose, and also increase the value of the index of insulin resistance HOMA-IR (p<0.001). No significant differences in age and BMI index were found between the study and control subjects. In the group of women with the true threat of pregnancy termination significantly increases the level of leptin (p=0.04), and there is also a decrease in the concentration of resistin (p=0.02). The level of adiponectin significant does not change.Summary: Compared with the control group, patients with RPL were more likely to have insulin resistance. In condition of the true threat of pregnancy termination increases the level of leptin and reduced the concentration of resistin, and is determined the development of pathological insulin resistance.